Mixing coefficients of ternary mixed electrolytes - Lim, Tiong-Koon (Malaysian Journal of Science (MJS), 1995)
The cluster expansion theory is used to explain ternary mixed electroytes having a common ion. The mixing coefficients have been studied and their inter relationships are reported. Their possible applications to the calculation of activity coefficients and osmotic coefficients are shown. Higherorder limiting laws are also discussed.